Update on the Global Initiative for Chronic Obstructive Lung Disease (GOLD 2023) - Adrianison, Adrianison; Simbolon, Rohani Lasmaria; Simatupang, Elvando Tunggul Mauliate (Jurnal Respirologi Indonesia, 2024)
The overall increase in morbidity and mortality associated with chronic obstructive pulmonary disease (COPD) is inextricably linked to the concept of Global Initiative for Chronic Obstructive Lung Disease (GOLD) updates. An element of every GOLD update is directed toward policymakers, healthcare professionals, and people in general in order to evaluate the immediate and prolonged consequences of COPD. At this time, international interest is focused on the acceleration of the GOLD 2022 update to GOLD 2023 in an effort to enhance clinical management approaches for COPD, including individualized and comprehensive COPD treatment. The GOLD 2023 update will encompass the following aspects: definition and taxonomy, screening and case identification, diagnosis pathway, pharmacological and non-pharmacological approaches to managing stable COPD, and exacerbation management, as discussed in this review. GOLD 2023 explains that the diagnosis of emphysema has been classified as a pathologic diagnosis, in comparison with GOLD 2022. In the meantime, the clinical and epidemiological diagnosis of COPD is chronic bronchitis. The risk factor for tobacco smoke, which was once thought to be the primary cause of COPD, is described in GOLD 2023, together with the most recent taxonomy that has been developed to identify additional contributing components. The word "GET", which refers to the interaction of three risk factors-gene (G), environment (E), and lifetime (T)-that can cause lung damage and accelerate the aging or development of the lungs, is also linked to the most recent taxonomy of COPD. The switch from the "ABCD" approach to the "ABE" method for diagnosis and management of stable COPD is another significant modification included in the GOLD 2023 update. The number of COPD cases worldwide is expected to rise in the upcoming years as an outcome of long-term exposure to risk factors. Consequently, with the goal of increasing patient survival rates, GOLD 2023 highlights the significance of screening and early case discovery through the provision of non-pharmacological care.